Intangible Cultural Heritage, Folklorists, and TCPs in the Hawaiian Context - Magat, Margaret (Material Culture Review, 2016)
In the world of cultural resource management, the work is often done by archaeologists and policy makers. Ethnographic studies or surveys of traditional cultural properties are usually conducted by individuals other than a trained folklorist or ethnographer. Yet in such studies of cultural impact assessment or projects involving federal funding such as Section 106 where consultation with the community is required in order to identify traditional cultural properties, folklorists with their understanding of the intangible as well as the material aspects of culture are particularly poised to answer the challenges in working with cultural properties. The notion of “cultural attachment” which integrate both the tangible and intangible (Maly 1999) often poses a challenge to those used to dealing just with the physical dimensions of material culture. In Hawai‘i, where natural resources such as hills or mountains as well as ocean currents are seen as cultural resources, there is often conflict between the community and those seeking to develop the place. Hawaiian living traditions include the cultural practice of mo‘olelo (stories, knowledge, opinion) surrounding wahi pana (sacred, legendary place), which anchor the intangible living traditions to a physical place or site which can qualify as a traditional cultural property. The conflicts tend to arise when those in cultural resource management fail to understand the critical intertwining of the intangible cultural heritage with the visible environment seen by Hawaiians in a different light. This paper explores the field of cultural resource management and how a folklorist’s understanding of “cultural attachment” and world view can assist in the understanding of traditional cultural properties which are intertwined with the intangible cultural heritage of living Hawaiians.